2011
DOI: 10.1159/000321813
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding after Percutaneous Coronary Intervention

Abstract: Percutaneous coronary intervention (PCI) is now performed in a wide range of patients with coronary artery disease. Complications of PCI include in-stent re-stenosis and in-stent thrombosis. According to the recent 2005 guidelines of the American College of Cardiology/American Heart Association/Society for Cardiovascular Angiography and Interventions, dual antiplatelet therapy with low-dose aspirin and thienopyridine derivatives such as ticlopidine and clopidogrel should be used in patients who have undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 97 publications
1
17
0
Order By: Relevance
“…A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22). In the present study, a univariate analysis focused on prescribed medications indicated that low-dose aspirin, antithrombotic drugs and corticosteroids are exacerbating factors for bleeding gastric and/or duodenal ulcers in elderly patients compared with nonelderly patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22). In the present study, a univariate analysis focused on prescribed medications indicated that low-dose aspirin, antithrombotic drugs and corticosteroids are exacerbating factors for bleeding gastric and/or duodenal ulcers in elderly patients compared with nonelderly patients.…”
Section: Discussionmentioning
confidence: 67%
“…The relationship between H. pylori infection and aspirin-related peptic ulcers is controversial. Some studies have indicated that H. pylori infection exacerbates aspirin-induced peptic ulcers that are reduced by eradication (20,33,34), while other studies have reported that H. pylori infection is not a risk factor for the development of aspirin-induced peptic ulcers (34)(35)(36). The results of the present study showing a decrease in the rate of H. pylori infection and an increase in the rate of aspirin use in elderly bleeding ulcer patients suggest that the risk of aspirin-induced bleeding is reduced in H. pylori-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of PUD bleeding in these patients has been attributed to nonsteroidal anti-inflammatory drug (NSAID) induced damage to the upper GI tract mucosa coupled with NSAID ± thiopyridine induced platelet inhibition and anticoagulation. (19, 20) We therefore conclude that an upper endoscopic examination is the best initial test in LVAD patients presenting with acute GIB, and provides the highest likelihood of finding a source for the bleed.…”
Section: Discussionmentioning
confidence: 74%
“…Gastrointestinal bleeding (GIB) is an important complication after PCI. Several studies have shown that incidence of GIB in patients undergoing PCI ranges from 0.4% to 4.3% (Nadatani et al, ; Tanigawa et al, ; Toyokawa et al, ; Nikolsky, Mehran, & Stone, ; Nikolsky, Stone, et al, ; Ng et al, ). Major bleeding can reduce blood volume, increase heart rate, and decrease myocardial perfusion, so antiplatelet therapies have to be changed after bleeding.…”
Section: Introductionmentioning
confidence: 99%